IMPROVING STUDENTS’ VOCABULARIES IN 3RD GRADE OF ELEMENTARY SCHOOL PENGANJURAN 4 USING COCOMELON YOUTUBE CHANNEL - Dinda Widya Castrena Dharma Putri; Moch. Ardi Setyawan; Rizki Nurfida Pambayun (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Many schools and courses offer English lessons. The four skills of English are speaking, reading, writing, and listening. Vocabulary is a tool to help with all four of these talents. To become proficient in the four areas of English language acquisition—speaking, listening, reading, and writing—fear is an essential component.. Vocabulary is fundamental to the acquisition of all English skills. Vocabularies are sets of letters, words formed by a community of users. The objectives of the background is to prove that visual media using Cocomelon YouTube Channel could applied in learning vocabulary to increase ability of students and to get information how much increase vocabulary students using YouTube videos Cocomelon This research using quantitative methods The results of this research resulted in significant improvements and increased students' interest in learning English using Cocomelon. This research using quantitative methods The results of this research resulted in significant improvements and increased students' interest in learning English using Cocomelon